Juvenile Wood Versus Mature Wood Densities in Cedrus deodara (Roxb.) Loud. - Sharma, M. B.; Sharma, C. L. (Indian Forester, 2007)
The present study aims to examine the quantitative relationship between juvenile wood and mature wood densities in order to look for the possibility of predicting mature wood density from that of juvenile wood and vice-versa and also to find out the suitable stratum for the comparison of juvenile wood and mature wood densities in Cedrus deodara (Roxb.) Loud. It is observed that a positive and statistically highly significant correlation exist between mean of juvenile wood and mean of mature wood density in both whole ring and first-formed early wood. Also, the mean mature wood density is highly significantly correlated separately with each of the juvenile wood rings in both whole ring and first-formed early wood except ring 1 in case of whole ring. Thus, the mature wood density can be predicted at an early age from the wood density of juvenile wood rings by taking either whole-ring or first-formed early wood.